PERASAAN CINTA PADA WANITA DEWASA AWAL - Puhi, Sitti Rojiyah Nur Insyirah (Elsia: Jurnal Psikologi Manusia, 2024)
Understanding love can help individuals understand the relationship between an individual and their partner, at least each individual has several characteristics of love which when they are in a relationship and marriage require them to unite two or even more characteristics of love. The aim of this research is to explore the meaning of love for women who are in the early adult development stage. The criteria for participants in this study were women in the early adult development stage who were married. This research uses a type of phenomenological research by providing open questions to participants which then produces four themes from the data obtained, namely physical touch, expressions of love, attraction, and things related to love.